(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The construction time as well as the cost of construction has always carried attracted attention in Civil Engineering. It has been supplemented by various economical and rapid installation construction techniques and materials. The one of this on which i want to carry my research is Concrete Canvas. Concrete Canvas is a new revolutionary construction material. It is a flexible, cement impregnated material which hardens on hydration to form a thin, durable, retaught, water proof and fire resistant concrete layer. Simply the Concrete Canvas is a flexible concrete in the form like cloth which can very easily positioned and then just add water. After hydration the concrete cloth turns into hard, durable concrete structure within 24 hours.